Evolution of magnetism on a curved nano-surface. Issue 30 (10th July 2015) - Merkel, D. G.; Bessas, D.; Zolnai, Z.; Rüffer, R.; Chumakov, A. I.; Paddubrouskaya, H.; Van Haesendonck, C.; Nagy, N.; Tóth, A. L.; Deák, A.
Abstract : The role of nanoparticle size, interparticle distance and magnetic layer thickness on the formation of magnetic nanostructures was studied. Individual magnetic behaviour was found for the 400 nm spheres and a collective magnetic structure for the 25 nm balls where magnetic domains spread over several particles. Abstract : To design custom magnetic nanostructures, it is indispensable to acquire precise knowledge about the systems in the nanoscale range where the magnetism forms. In this paper we present the effect of a curved surface on the evolution of magnetism in ultrathin iron films. Nominally 70 Å thick iron films were deposited in 9 steps on 3 different types of templates: (a) a monolayer of silica spheres with 25 nm diameter, (b) a monolayer of silica spheres with 400 nm diameter and (c) for comparison a flat silicon substrate. In situ iron evaporation took place in an ultrahigh vacuum chamber using the molecular beam epitaxy technique. After the evaporation steps, time differential nuclear forward scattering spectra, grazing incidence small angle X-ray scattering images and X-ray reflectivity curves were recorded. In order to reconstruct and visualize the magnetic moment configuration in the iron cap formed on top of the silica spheres, micromagnetic simulations were performed for all iron thicknesses. We found a great influence of the template topography on the onset of magnetism and on the developed magnetic nanostructure. We observed an individual magnetic behaviour for the 400 nm spheres which was modelled by vortex formation and a collective magnetic structure for the 25 nm spheres where magnetic domains spread over several particles. Depth selective nuclear forward scattering measurements showed that the formation of magnetism begins at the top region of the 400 nm spheres in contrast to the 25 nm particles where the magnetism first appears in the region where the spheres are in contact with each other.